Hubungan Tingkat Demensia dengan Pemenuhan Kebutuhan Activity Of Daily Living (ADL) pada Lansia di Panti Puncang Gading - Cindy Cahyaningrum; Iwan Ardian; Nutrisia Nu’im Haiya (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Dementia is a major health problem among older adults and has a substantial impact on the ability to perform Activity of Daily Living. This study aimed to examine the relationship between the level of dementia and the fulfillment of Activity of Daily Living among older adults living in Panti Puncang Gading. A quantitative analytic approach with a cross-sectional design was employed. The study involved 67 older adults selected through purposive sampling from eligible residents. Dementia severity was assessed using the Short Portable Mental Status Questionnaire, while functional independence was measured using the Barthel Index. Data were analyzed using Somers’ d test to determine the strength and direction of the association between variables. The results indicated that most respondents experienced severe dementia, while the majority demonstrated mild dependency in daily living activities. Statistical analysis revealed a significant negative correlation between dementia level and Activity of Daily Living fulfillment, indicating that higher dementia severity was associated with lower functional independence. These findings highlight the critical role of cognitive function in maintaining daily living abilities and emphasize the importance of routine cognitive and functional assessments to support evidence-based gerontological nursing care in long-term care facilities.